2021
DOI: 10.3389/fendo.2021.761397
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride and Glucose Index and Sex Differences in Relation to Major Adverse Cardiovascular Events in Hypertensive Patients Without Diabetes

Abstract: IntroductionStudies from recent decades have suggested that women have a lower risk of cardiovascular disease than men due to their characteristics, but hyperglycemia and hyperinsulinemia caused by IR (insulin resistance) might reverse this gender-protective effect. This study examined whether there were sex differences in the relationship between IR [evaluated by triglyceride and glucose index (TyG index)] and major adverse cardiovascular events (MACEs) in hypertensive patients without diabetes.MethodsThis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
0
28
1
Order By: Relevance
“…All insulin replacement markers showed that good association with HOMA-IR of both sexes, and the association between female and HOMA-IR was stronger than that of male [ 38 ]. However, some studies have found that there was no sex difference between the TyG index and MACEs in patients with hypertension [ 39 ]. There has been an investigation of the association between the TyG index and the early stages of subclinical atherosclerosis (SA) between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…All insulin replacement markers showed that good association with HOMA-IR of both sexes, and the association between female and HOMA-IR was stronger than that of male [ 38 ]. However, some studies have found that there was no sex difference between the TyG index and MACEs in patients with hypertension [ 39 ]. There has been an investigation of the association between the TyG index and the early stages of subclinical atherosclerosis (SA) between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that all insulin replacement markers have a good correlation with HOMA-IR of both sexes, and the correlation between female is stronger than that of male [40]. However, some studies have found that there was no gender difference between the TyG index and MACEs in patients with hypertension [41]. There is an investigation of the association between the TyG index and the early stages of subclinical atherosclerosis (SA) between the sexes.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…HFpEF was diagnosed as per the diagnostic criteria for HFpEF in the 2016 European Society of Cardiology guidelines. 14 Inclusion criteria are as follows: (1) | 937 congenital bicuspid aortic valve, ebstein anomaly, congenital aorticainus aneurysm, coronary artery fistulae, congenital tetralogy of Fallot); (4) severe heart valve disease (mitral stenosis, mitral regurgitation, aortic stenosis, and aortic incompetence); (5) restrictive cardiomyopathy; (6) hypertrophic cardiomyopathy; (7) pericardial diseases (acute pericarditis and constrictive pericarditis); (8) heart failure due to noncardiogenic factors (severe infection, anemia, and diseases of blood system); (9) thyroid dysfunction (hyperthyroidism and hypothyroidism); (10) severe liver damage (glutamic-propylene and glutamic-oxalacetic transaminases higher than three times the upper limit of normal); (11) heavy renal impairment (glomerular filtration rate <60 ml min −1 [1.73 m 2 ] −1 ); (12) drugs affecting blood glucose and blood lipids used before admission.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…A recent study has demonstrated that TyG index is positively associated with type 2 diabetes and the incidence rate of cardiovascular diseases 11 . It has also been documented that TyG index is related to poor prognoses in patients with heart failure and type 2 diabetes 12 . However, little is known about the correlation between TyG index and the occurrence of HFpEF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation